Trityl-nitroxide biradicals as unique molecular probes for the simultaneous measurement of redox status and oxygenation - Liu, Yangping (2009)
Novel trityl-nitroxide biradicals were synthesized and exhibited enhanced sensitivity and stability for rapid and simultaneous measurement of redox status and oxygenation by electron paramagnetic resonance spectroscopy.